“İʿrâbu’l-Kur’ân” ve “Meʿâni’l-Kur’ân” Eserleri Bağlamında Ebû Caʿfer enNehhâs’ın Tefsir Metodu ve Kur’ân İlimlerine Yaklaşımı - Karaalp, Cahit (Muş Alparslan Üniversitesi, 2021)
Abu Jafer an-Nahhas endeavored to interpret Qur’an nicely by elaborating basic subjects of tafsir in the Mâni'l-Quran and I?râbu’l-Quran. As a Tafsir, the Irâbu'l-Qur'an is important as it is the first work that systematically evaluates the Quran entirely regarding i'rab. Although the "Meani'l-Qur'an" which was written before the "I?râbu’l-Qur'an" has not reached today in its full form, these works complement each other. The sparcity of research on methodology of Nehhas'tafsir in the academic world in our country, particularly on the "I'râbu'l-Qur'an" and "Meani'l-Quran" tafsirs urge us to explore on this subject. In our work, we aim to elaborate the interpretative aspect of Abu Jafar an-Nahhas, to present his distinctives and the information about his methodology.

Ebu Cafer en-Nehhâs, Me?âni’l-Kur’ân ve İ?râbu’l-Kur’ân isimli eserlerinde tefsir ilminin temel konularını ustalıkla işleyerek Kur’ân’ı tefsir etmeye çalışmıştır. Kur’ân’ı i’rab açısından baştan sona sistematik bir şekilde değerlendiren ilk eser olması hasebiyle İ?râbu’l-Kur’ân tefsiri önem arz etmektedir. “İ?râbu’l-Kur’ân” tefsirinden önce kaleme alınan “Meani’l-Kur’ân” tefsiri günümüze tam hali ile gelmemiş olsa da “İrâbu’l-Kur’ân” tefsiri ile birbirini bütünler niteliktedir. Ülkemizde akademi dünyasında Nehhâs’ın tefsir metodolojisini konu alan kapsamlı bir çalışmanın olmaması bir de “İ’râbu’l-Kur’ân” ve “Meani’l-Kur’ân” tefsirleri hakkında çok az bir çalışmanın bulunması bizi bu konuda bir çalışma yapmaya sevk etmiştir. Makalemizde Ebu Cafer en-Nehhâs’ın tefsirci yönü üzerinde durmayı, metodolojisi hakkında bilgi vermeyi ve özgün taraflarını ortaya koymayı hedeflemekteyiz.
The Methodology of Abu Jafar an-Nahhâs and his approach to Qur'anic knowledge in the Context of the "I?râbu'l-Qur'an" and "Me?ânı'l- Qur'an "
anemon
Keywords: Tafsir; Qur'an; Nahhas; İ'rab; Me'ani; Tefsir; Kur'an; Nehhâs; İ'râb; Meânî